Intent to Volunteer of Graduate Students in Multi-Sectoral Areas as Inputs for Curriculum Enhancement in Higher Education Institutions - Molina , Jayson P; Camara, Jun S; Cancino, Edwin C (ASEAN Multidisciplinary Research Journal, 2023)
Sectoral area volunteerism could be enhanced through the lens of intent to volunteer along these areas, yet no study has been done to measure this among potential Filipino volunteers. This study identified the level of intent that Filipinos have for each sectoral area using graduate students (n=124) of a state university in Pangasinan, Philippines as participants in 2022 and across 161 areas for 13 sectors based on the Philippine National Volunteer Service Coordinating Agency (PNVSCA). Findings revealed that the participants have intentions to volunteer in all areas of all the sectors and with the sectors on Education, Culture and Values, Health, Social Services, Governance and Public Administration, Science, Technology and Innovation, and Environment receiving means interpreted with high intention. While Peace and Security, Safety and Resilience, Justice, Agriculture, and Fishery, and Industry and Services received means not interpreted as high, an intent to volunteer along these areas was also reported. These findings should inform higher education institutions the potential of engaging our graduate students in opportunities to volunteer along these sectoral areas and which enabled the researchers to propose a curricular enhancement for higher education with seven core elements that include emphasis on internal and external partnership for opportunities and linkages.